2012
DOI: 10.1007/s11060-012-0865-9
|View full text |Cite
|
Sign up to set email alerts
|

A retroperitoneal NF1-independent malignant peripheral nerve sheath tumor with elevated serum CA125: case report and discussion

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are usually located in the trunk, extremities, head, or neck, and most occur with neurofibromatosis type 1 (NF1; von Recklinghausen's disease). No biomarkers have previously been found to be associated with their progression. Retroperitoneal NF1-independent MPNSTs are rare; they are considered to be less aggressive and to have better prognoses compared to NF1-related tumors. Currently, en bloc excision is the only consensus treatment approach. In a 27-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…An MPNST arising in the abdomen is very rare, and to the best of our knowledge, only a few cases of retroperitoneal MPNSTs have been reported (7,8). Various neoplastic diseases develop in the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
“…An MPNST arising in the abdomen is very rare, and to the best of our knowledge, only a few cases of retroperitoneal MPNSTs have been reported (7,8). Various neoplastic diseases develop in the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous treatment, as used in this case, provides a viable but underutilized option. We reviewed the literature and found prior reports of percutaneous treatment of PNSTs in only seven patients [ 4 , 6 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second patient had a benign, non-operated retroperitoneal schwannoma that also decreased in size and was stable for 27 months [ 4 ]. Yan et al [ 9 ] utilized microwave ablation as a salvage procedure in a patient with a large abdominal malignant peripheral nerve sheath tumor (MPNST) that recurred within two months of surgical resection. Although imaging studies immediately post-ablation showed necrosis in the tumor, the patient died within three months of the procedure [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expected management with routine imaging and surgical resection, possible alternative treatment options for non-cutaneous PNSTs include cryoablation, radiosurgery, microwave ablation and radiofrequency ablation. There are only single reports of percutaneous treatment of PNSTs (42)(43)(44)(45)(46)(47). The treatment objective for BPNSTs within main peripheral nerves should be lesion control and not complete ablation, since most normal fibers travel within the capsule of the tumor.…”
Section: Treatment Of Pnstsmentioning
confidence: 99%